Sodium alginate/β-cyclodextrin reinforced carbon nanotubes hydrogel as alternative adsorbent for nickel(ii) metal ion removal - Zakaria, Aiza Farhani; Kamaruzaman, Sazlinda; Abdul Rahman, Norizah; Yahaya, Noorfatimah (Multidisciplinary Digital Publishing Institute, 2022)
Water pollution issues, particularly those caused by heavy metal ions, have been significantly growing. This paper combined biopolymers such as sodium alginate (SA) and β-cyclodextrin (β-CD) to improve adsorption performance with the help of calcium ion as the cross-linked agent. Moreover, the addition of carbon nanotubes (CNTs) into the hybrid hydrogel matrix was examined. The adsorption of nickel(II) was thoroughly compared between pristine sodium alginate/β-cyclodextrin (SA-β-CD) and sodium alginate/β-cyclodextrin immobilized carbon nanotubes (SA-β-CD/CNTs) hydrogel. Both hydrogels were characterized by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) spectral analysis, field emission scanning electron microscopy (FESEM), electron dispersive spectroscopy (EDX), thermogravimetric analysis (TGA) and Brunauer–Emmett–Teller (BET) surface area analysis. The results showed SA-β-CD/CNTs hydrogel exhibits excellent thermal stability, high specific surface area and large porosity compared with SA-β-CD hydrogel. Batch experiments were performed to study the effect of several adsorptive variables such as initial concentration, pH, contact time and temperature. The adsorption performance of the prepared SA-β-CD/CNTs hydrogel was comprehensively reported with maximum percentage removal of up to 79.86% for SA-β-CD/CNTs and 69.54% for SA-β-CD. The optimum adsorption conditions were reported when the concentration of Ni(II) solution was maintained at 100 ppm, pH 5, 303 K, and contacted for 120 min with a 1000 mg dosage. The Freundlich isotherm and pseudo-second order kinetic model are the best fits to describe the adsorption behavior. A thermodynamic study was also performed. The probable interaction mechanisms that enable the successful binding of Ni(II) on hydrogels, including electrostatic attraction, ion exchange, surface complexation, coordination binding and host–guest interaction between the cationic sites of Ni(II) on both SA-β-CD and SA-β-CD/CNTs hydrogel during the adsorption process, were discussed. The regeneration study also revealed the high efficiency of SA-β-CD/CNTs hydrogel on four successive cycles compared with SA-β-CD hydrogel. Therefore, this work signifies SA-β-CD/CNTs hydrogel has great potential to remove Ni(II) from an aqueous environment compared with SA-β-CD hydrogel.